Antifungal Activity of Dried Extracts of Anise (Pimpinella anisum L.) and Star anise (Illicium verum Hook. f.) Against Dermatophyte and Saprophyte Fungi - Yazdani, D.; Rezazadeh, S.; Amin, G.; Zainal Abidin, M. A.; Shahnani, S.; Jamalifar, (2009)
Background: Medicinal plants synthesize a vast array of secondary metabolites that are important for human life. For medicinal purpose, antimicrobial activity of substances derived from plant extracts has been recognized for many years. Pimpinella anisum L.(Apiaceae) and Illicium verum Hook. f. (Illiciaceae) plant species, have been used for treatment of infectious diseases in Iranian traditional medicine. Objective: In this study methanol extracts of Pimpinella anisum L. (Apiaceae) and Illicium verum Hook. f. (Illiciaceae), were tested for their potential antifungal activities. Methods: Methanolic extracts were dried by freeze drying method, Minimum Inhibitory Concentration (MIC) was was determined according to agar dilution method and Minimum Fungicidal Concentration (MFC) was determined by incorporating various concentrations of extracts (2-256 mg/ml) in Sabouraud dextrose agar (SDA) in tubes against 4 dermatophyte and one saprophyte fungi. Results: The extracts of anise seeds inhibited only dermatophyte species, while extracts of star anise fruits inhibited growth of all dermatophytes and saprophytes. MIC and MFC for each extracts were different and MFC was higher than MIC for all species. Conclusion: As a result of this experiment, these plants can be candidate for further studies due to their antifungal potencies.